Maladministrasi dalam Penyaluran Bantuan Sosial Akibat Ketidaktepatan Data Penerima di Dinas Sosial Kota Gorontalo: Kajian Hukum Administrasi Negara - Raihan A. Hanasi; Nadia Putri Zakaria; Nadia Sawali; Susanti Abdullah; Nia Rahmadani Bangko (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the issue of maladministration in the distribution of social assistance that occurred in Padebuolo Village, Gorontalo City, involving two elderly citizens with visual impairment named Aisyah Katili and Hapisah Katili. These two citizens, who should have been registered as priority recipients in the social welfare data system, failed to receive their rightful assistance for a considerable period, allegedly due to data manipulation and misconduct by certain village-level officials. This study employs a normative-empirical approach by analyzing the case from the perspective of State Administrative Law, particularly regarding the principles of maladministration, general principles of good governance, and the mechanisms for protecting the rights of social assistance beneficiaries. The findings indicate that the actions or negligence causing the cessation of social assistance distribution to these vulnerable groups fulfill the elements of maladministration as regulated under Law Number 25 of 2009 on Public Services and Law Number 37 of 2008 on the Ombudsman of the Republic of Indonesia. This research recommends comprehensive reform of beneficiary data governance, strengthening internal supervisory mechanisms at every level of government, and enforcement of both administrative and criminal sanctions against officials proven to have committed irregularities in social assistance management.